The clinical and financial burden of pre-emptive management of cytomegalovirus disease after allogeneic stem cell transplantation—implications for preventative treatment approaches - Jain, Natasha A.; Lu, Kit; Ito, Sawa; Muranski, Pawel; Hourigan, Christopher S.; Haggerty, Janice; Chokshi, Puja D.; Ramos, Catalina; Cho, Elena; Cook, Lisa; Childs, Richard; Battiwalla, Minoo; et al. (Cytotherapy (Oxford, England), 2014)
Although cytomegalovirus (CMV) infection after allogeneic stem cell transplantation (SCT) is rarely fatal, the management of CMV by pre-emptive medication for viral reactivation has toxicity and carries a financial burden. New strategies to prevent CMV reactivation with vaccines and antiviral T cells may represent an advance over pre-emptive strategies but have yet to be justified in terms of transplantation outcome and cost. We compared outcomes and post-transplantation treatment cost in 44 patients who never required pre-emptive CMV treatment with 90 treated patients undergoing SCT at our institute between 2006 and 2012. Eighty-one subjects received CD34+ selected myeloablative SCT, 12 umbilical cord blood transplants, and 41 T-replete non-myeloablative SCT. One hundred nineteen patients (89%) were at risk for CMV because either the donor or recipient was seropositive. Of these, 90 patients (75.6%) reactivated CMV at a median of 30 (range 8–105) days after transplantation and received antivirals. There was no difference in standard transplantation risk factors between the two groups. In multivariate modeling, CMV reactivation >250 copies/mL (odds ratio = 3, P < 0.048), total duration of inpatient IV antiviral therapy (odds ratio = 1.04, P < 0.001), type of transplantation (T-deplete vs. T-replete; odds ratio = 4.65, P < 0.017) were found to be significantly associated with increased non-relapse mortality. The treated group incurred an additional cost of antiviral medication and longer hospitalization within the first 6 months after SCT of $58,000 to $74,000 per patient. Our findings suggest that to prevent CMV reactivation, treatment should be given within 1 week of SCT. Preventative treatment may improve outcome and have significant cost savings.